Anatomical and Clinical Characteristics of Scalp Acupuncture Systems: a Scoping Review and Synthesis - Svetlana Wise; Ava Lorenc (Medical Association of Pharmacopuncture Institute, 2023)
Scalp acupuncture is a therapeutic procedure that involves inserting needles into the scalp to treat various medical conditions, including pain and neurological and psychological disorders. The inter-system variability of scalp acupuncture limits secondary analysis and evidence synthesis, delaying its inclusion into evidence-based healthcare policies and establishment as a treatment intervention recognized by Western medicine. This scoping review aimed to identify the range of scalp acupuncture systems, systematically collect and summarize information on their general, anatomical, and clinical characteristics, and build a framework for understanding scalp acupuncture systems. This review included all English-language publications on scalp acupuncture applied to treat any health condition in humans. Extensive searches were conducted across bibliographic databases, journals, trial registries, and supplementary sources. The detailed general, anatomical, and clinical application characteristics of 19 scalp acupuncture systems were extracted. Data were collected and analyzed using charting and image manipulation software. Framework synthesis was performed using the Standard International Acupuncture Nomenclature Scalp Acupuncture as an a priori framework. The review revealed that the heterogeneity related to scalp acupuncture methods can be attributed to the high variability among the theoretical bases of different systems, intersystem mismatch in anatomical locations of treatment points and areas on the scalp, and inconsistencies in the methods used for locating them. These discrepancies in anatomical and clinical features have limited the synthesis and development of a framework for scalp acupuncture. Discussion and agreement on the anatomical locations of scalp stimulation areas, identification of methods for precise positioning of acupuncture areas on the scalp, and further exploration of theoretical bases will aid in the standardization of scalp acupuncture and improve the quality of research in this area.